Determinants of functional capacity and work ability post SARS-COV-2 infection in miners - Ndlovu, Vusimuzi (Department of Public Health and Family Medicine, 2026)
Background: Insufficient data exists on the sequelae of COVID-19 and its impact on function and work ability among workers. The aim of this study was to investigate the determinants of functional capacity and work ability in miners following COVID-19 disease. Methods: This cross-sectional study recruited 204 mine workers employed at a ferromanganese mine in the Northern Cape province of South Africa with a confirmed laboratory diagnosis of COVID-19 within the past 12 months. Study instruments included a socio-demographic questionnaire, Post COVID-19 Functional Scale (PCFS), Work Ability Index (WAI), chest radiograph and the Two-minute Walk Test (TMWT). Data analysis was done using STATA version 16 to generate univariate and multivariate quantile regression models. Results: The majority (74%) of the participants were males with a mean age of 38.8 years and employed in the mining department (46%) as operators. A third were current smokers (35%), and obese (36%). The most commonly reported acute COVID-19 symptoms were sore throat (56%), cough (43%), and anosmia (34%). Almost all the participants had reported having two or more episodes of COVID-19 which was of a mild form (64%). Most (86%) returned to work within 14 days of diagnosis. None of the miners had an abnormal PCFS score, nor did they have poor WAI scores. Aside from living arrangements (living with a spouse), none of the socio-demographic or occupational factors were associated with COVID-19 disease severity. Unlike for COVID-19 disease, female sex was significantly associated (p<0.001) with poor performance on the TMWT in the simple regression models. After adjusting for disease severity and sex in the multivariate models, no significant association was observed between COVID-19 disease and the TMWT distance. Conclusion: This study found limited evidence of impaired functional capacity and work ability in miners following COVID-19 disease within one year of SARS-CoV-2 infection. Furthermore, only female sex, but not COVID-19 was associated with impaired functional ability.